Effect of Top-dressing and Planting Density on the Number of Spikelets and Yield of Rice Cultivated with Nitrogen-free Basal Dressing - Truong Hop Tac; Mitsugu Hirano; Shigeru Iwamoto; Eiki Kuroda; Takao Murata (Plant Production Science, 1998)
The effects of nitrogen-free basal dressing (BNo) and top-dressing on the growth and yield of two rice varieties, Akitakomachi and Hitomebore, planted at a standard density (22.2 hills m−2) and sparse density (16.7 hills m−2) were examined. The maximum number of stems and the number of panicles per unit area were lower in both BNo plots with a standard planting density (BNo22) and sparse planting density (BNol7) than in the control plot with standard nitrogen dressing and standard planting density (CONT) in both varieties. The number of panicles and spikelets per unit area was lower in both BNo22 and BNo 17 than in CONT, but the number of spikelets per panicle in BNo 17 was significantly higher than that in CONT, although that in BNo22 was not. In BNo22, the percentage of ripened grains and 1,000 grain weight were significantly higher than those in CONT, but in BNo 17, 1,000 grain weight was similar to that in CONT, although the percentage of ripened grains was higher than that in CONT. Grain yield in both BNo22 and BNo 17 was not significantly different from that in CONT, and that in BNo 17 was 660 and 710 g m−2 in Akitakomachi and Hitomebore, respectively. The leaf area index was lower and crop growth rate was higher in both BNo22 and BNol7 than in CONT at the grain-filling stage. The net assimilation rate and specific leaf weight were significantly higher in BNo22 and BNo 17 than in CONT at the panicle formation and grain-filling stages, respectively. Nitrogen top-dressing at the neck node differentiation stage was found to be very useful for the cultivation of these rice varieties under BNo with sparse planting density in the Tohoku district.